Candidate antirheumatic genotherapeutic plasmid constructions have low immunogenicity - T. S. Nepomnyashchikh; T. V. Tregubchak; S. N. Yakubitskiy; O. S. Taranov; R. A. Maksyutov; S. N. Shchelkunov (Вавиловский журнал генетики и селекции)
Rheumatoid arthritis (RA) is a serious systemic disease of connective tissue, mainly affecting joints but also with different extra-articular manifestations. In the course of RA the degenerative changes occur in cartilage surfaces of affected joints and also in subchondral bone tissue, joints get deformed and lose their mobility. RA affects about 1 % of the global human population. Biological therapy with recombinant protein inhibitors of inflammatory cytokines is an effective and well-accepted treatment of RA. TNF inhibitors such as recombinant receptors or monoclonal antibodies are the most widely used biotherapeutics in clinical practice. However, this treatment has some serious side effects. The patients treated with TNF inhibitors are more susceptible to infection diseases, they are also at higher risk of developing neoplastic or autoimmune disorders. Biotherapeutics become less effective or even lose their efficiency with evoking specific antidrug antibodies. These drawbacks are in general associated with repeated systemic injections of large amounts of recombinant protein required to achieve the therapeutic efficacy. Genetic therapy might provide a good and effective solution. Viral genes coding for immunomodulatory factors could be used to create new gene therapy products to treat RA and other human disease. Poxviruses, as compared to other viral families, have an unprecedentedly rich set of such immunomodulatory genes. In particular, they have genes encoding TNF-binding proteins. Previously in a variety of laboratory models we have shown that recombinant TNF-binding protein CrmB can effectively block TNF. In this work we demonstrated that candidate antirheumatic genotherapeutic plasmid constructions encoding poxviral TNF-binding proteins have low immunogenicity.